Administrasi Pembelajaran Guru dalam Penerapan Kurikulum Merdeka di Madrasah Ibtidaiyah - Wahyuni, Nur; Hidayah, Nurul; Sahwan, Risa Ardila Sari (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study employed a library research method with a qualitative descriptive approach. Data were obtained from various scientific literature sources, such as books, national and international journals, policy documents, and relevant research findings, which were critically analyzed through stages of reduction, classification, synthesis, and interpretation. The results indicate that learning administration plays a crucial role in establishing an effective, innovative, and student-centered teaching system. Teachers are required to possess the skills to plan, implement, and evaluate learning that adapts to the madrasah context and student characteristics. The implications of this study emphasize that the successful implementation of the Independent Curriculum is highly dependent on teacher professionalism in managing learning administration adaptively and based on Islamic values. The novelty of this research lies in strengthening the relationship between learning administration and Islamic educational spirituality, which can support the creation of an independent learning ecosystem in Madrasah Ibtidaiyah.